Eotaxin-1/CCL11 promotes cellular senescence in human-derived fibroblasts through pro-oxidant and pro-inflammatory pathways - Lavandoski, Patrícia; Pierdoná, Vinícius; Maurmann, Rafael Moura; Grun, Lucas Kich; Guma, Fatima T. C. R.; Barbé-Tuana, Florencia María (Frontiers in Immunology, 2023)
Introduction Eotaxin-1/CCL11 is a pivotal chemokine crucial for eosinophil homing to the lungs of asthmatic patients. Recent studies also suggest that CCL11 is involved in the aging process, as it is upregulated in elderly, and correlated with shorter telomere length in leukocytes from asthmatic children. Despite its potential pro-aging effects, the precise contribution of CCL11 and the underlying mechanisms involved in the promotion of cellular senescence remains unclear. Therefore, the primary goal of this study was to explore the role of CCL11 on senescence development and the signaling pathways activated by this chemokine in lung fibroblasts. Methods To investigate the targets potentially modulated by CCL11, we performed an in silico analysis using PseudoCell. We validated in vitro the activation of these targets in the human lung fibroblast cell line MRC-5 following rhCCL11 exposure. Finally, we performed differential gene expression analysis in human airway epithelial cells of asthmatic patients to assess CCL11 signaling and activation of additional senescent markers. Results Our study revealed that eotaxin-1/CCL11 promote reactive oxygen secretion (ROS) production in lung fibroblasts, accompanied by increased activation of the DNA damage response (DDR) and p-TP53 and γH2AX. These modifications were accompanied by cellular senescence promotion and increased secretion of senescence-associated secretory phenotype inflammatory cytokines IL-6 and IL-8. Furthermore, our data show that airway epithelial lung cells from atopic asthmatic patients overexpress CCL11 along with aging markers such as CDKN2A (p16INK4a) and SERPINE1. Discussion These findings provide new insights into the mechanisms underlying the pro-aging effects of CCL11 in the lungs of asthmatic patients. Understanding the role of CCL11 on senescence development may have important implications for the treatment of age-related lung diseases, such as asthma.